2008
DOI: 10.1186/1471-2334-8-138
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of larval mosquitoes by Acilius sulcatus (Coleoptera: Dytiscidae)

Abstract: Background: Problems associated with resistant mosquitoes and the effects on non-target species by chemicals, evoke a reason to find alternative methods to control mosquitoes, like the use of natural predators. In this regard, aquatic coleopterans have been explored less compared to other insect predators. In the present study, an evaluation of the role of the larvae of Acilius sulcatus Linnaeus 1758 (Coleoptera: Dytiscidae) as predator of mosquito immatures was made in the laboratory. Its efficacy under field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 21 publications
4
18
0
4
Order By: Relevance
“…The predation rate of predator species and the survival rates of An. gambiae larvae in habitats with and without refugia were similar to results found by other studies in Kenya and elsewhere [8,9,11,25]. In our experiments, all predators were shown to consume intermediate size prey (third instars larvae) at the highest rate.…”
Section: Discussionsupporting
confidence: 91%
“…The predation rate of predator species and the survival rates of An. gambiae larvae in habitats with and without refugia were similar to results found by other studies in Kenya and elsewhere [8,9,11,25]. In our experiments, all predators were shown to consume intermediate size prey (third instars larvae) at the highest rate.…”
Section: Discussionsupporting
confidence: 91%
“…This study, however shows that the nucleotide difference between the larval and deposited sequences correspond to adult stage were maximally 1-2% in Culicoides circumscriptus and Culicoides puncticollis. The results corroborate the findings in previous reports of molecular identification of Culicoides larvae which showed that the nucleotide differences between the larval and deposited sequences were maximally 3-4% in Culicoides kibunensis and Culicoides verbosus [13].…”
Section: Culicoides Speciessupporting
confidence: 91%
“…On the one hand, and from the ecological side, the numbers of larvae surpass the number of adults. Thus, the identification of larval instars is essential to predict the role of species in the environment [13,14]. On the other hand, knowledge of the larval taxonomy provides clues about their diet and feeding habitats that cannot be obtained from the adult morphology [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…As generalist predators, dytiscids may feed on all available prey taxa and mosquito larvae will be only one prey among others however super-abundant. Many dytiscids are known to include mosquito larvae in their diet (Deding, 1988;Nilsson & Söderström, 1988;Nilsson & Svensson, 1994;Lundkvist et al, 2003;Medlock & Snow, 2008), and a few studies show that dytiscids may lower the mosquito larvae abundance in lab and in the field (Lundkvist et al, 2003;Aditya et al, 2006;Chandra et al, 2008).…”
Section: Discussionmentioning
confidence: 99%